The potential use of car windscreens for post-accident dose reconstruction in the periphery of nuclear installations - Norfadira, W.; Khandaker, Mayeen Uddin *; Abdul Sani, S. F.; Almugren, K.S.; Bradley, D.A. *; Sulieman, A.; Faruque, M. R. I.; Sayyed, M. I. (MDPI, 2020)
Cars of a variety of brands are usually parked at a fixed but increasing distance in the periphery of nuclear installations. Herein we focus on the potential use of car windscreens for post‐accident dose reconstruction from unplanned nuclear events and natural disasters, also in regard to unexpected events arising during large‐scale use of radioactive and nuclear materials. The situation requires identification of analytical techniques that could both readily and reliably be used to assess absorbed dose, sufficient to prompt remedial action where necessary. Samples from three widely used car brands—Honda, Toyota and Proton—are studied in respect of their thermoluminescence (TL) yield. Key TL dosimetric features in the gamma‐ray dose range of 1–100 Gy are examined. An ERESCO model 200 MF4‐RW X‐ray machine has also been used for energy response studies; a Harshaw 3500 TLD reader equipped with WinREMS software was used for the luminescence measurements. All brands exhibit linearity of TL yield versus dose, the samples from Honda showing the greatest response followed by that of the Toyota and Proton brands. The marked energy dependence reflects the effect of the strongly Z‐dependent photoelectric effect. Signal fading was investigated over a period of 28 days, the Toyota and Proton brand windshield glass showing a relatively low loss at 52.1% and 52.6% respectively compared to a 56.7% loss for that of the Honda samples. This work forms the first such demonstration of the potential of car windshield glass as a retrospective accident dosimeter.